2006
DOI: 10.1002/srin.200606444
|View full text |Cite
|
Sign up to set email alerts
|

Formability of High Strength Dual‐phase Steels

Abstract: The application of ferritic-martensitic dual-phase (DP) steels has become an increasing trend in the automotive industry due to the possibility to achieve significant weight reduction and fuel efficiency with improved crash performance while keeping the manufacturing costs at affordable levels. In order to meet the different design requirements of individual auto-body components, a wide variety of DP grades exhibiting different strength and ductility levels is currently industrially produced. Despite the numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…Balliger and Gladman 10) have shown that refining martensite islands in dual phase steels results in an increase in work hardening rate. Tsipouridis et al 11) revealed that the strength of dual phase steels can be improved via grain refinement while the ductility remains unaffected in a Mo-Cr alloyed steel. The yield ratio of 0.59 for a C-Mn UFG dual phase steel is comparable with the coarse grained counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balliger and Gladman 10) have shown that refining martensite islands in dual phase steels results in an increase in work hardening rate. Tsipouridis et al 11) revealed that the strength of dual phase steels can be improved via grain refinement while the ductility remains unaffected in a Mo-Cr alloyed steel. The yield ratio of 0.59 for a C-Mn UFG dual phase steel is comparable with the coarse grained counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been a very limited number of © 2011 ISIJ studies to develop UFG dual phase steels in plain low carbon steels. [11][12][13][14][18][19][20] Thus, the present work seeks to examine combinations of cold rolling and annealing processing steps to develop UFG dual phase structures in a plain low carbon steel with 0.17C and 0.74Mn (wt pct). A systematic study is presented to investigate the effect of initial structure and processing parameters such as heating rate and intercritical annealing time on the microstructure evolution and resulting mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Outro aspecto microestrutural, que pode ter deteriorado a capacidade de expansão de furo, foi a formação mais intensa de bandeamento de martensita nesta bobina em relação às demais avaliadas. Segundo a literatura [7], durante o processo de corte por puncionamento para a confecção da borda do furo, pode ocorrer a formação de microtrincas preferencialmente em volta e ao longo dessas bandas, acelerando a propagação de trincas durante os esforços de estiramento da borda. Na figura 6 são mostradas as correlações entre os resultados de expansão de furo e a fração volumétrica de bainita, ferrita e martensita.…”
Section: Discussionunclassified
“…The measurement of misorientation caused by mechanical polishing was conducted on a specially heat-treated coarse-grained dualphase steel (DP600) (Tsipouridis, 2006;Tsipouridis et al, 2006). The orientation of the large grains of ferrite in the steel DP600 is most likely not affected by the presence of grain and phase boundaries, as compared to the microstructures of the other more complex and fine-grained materials.…”
Section: Experimental Procedures and Materials Characterizationmentioning
confidence: 99%